A Study on The Suitability of Pumice Stone Powder As A Cementitious Material in Sustainable Green Concrete Production - Amenu, Teklu; Geremew, Anteneh; Ayene, Habtamu (International Journal of Sustainable Construction Engineering and Technology, 2023)
This experimental considered involves on the performance properties of pumice powder as a supplementary cementitious material for ordinary Portland cement materials. The results showed that the pumice powder can be categorized as a pozzolanic constituents according to the ASTM C 618 standard, its main chemical composition SiO2 + Al2O3 + Fe2O3 must be higher than 70% and it was confirmed as suitable for its potential use as a supplemental cementitious resources in the production of concrete materials. As the amount of replacement of cement by the pumice powder increases its workability and density become decreases, it’s delayed in setting time observed, and it requires more water to achieve standard consistency. At 25%, it was a weight reduction of up to 3.83% was observed, as a weight of cement substituted with powdered pumice, and the compressive strength of the powdered pumice specimens was replaced with a cement at different levels of 5wt%, 10wt%, 15wt%, 20wt%, and 25wt% cement resulted in a decrease after 7, 28, 56 and 90 days. In addition, it was observed in this study that its strength decreased with increasing curing age; however; replacing ordinary Portland cement with 5wt% to 10wt% pumice powder achieved the specified minimum compressive strength after a curing time of 28 days. But, a concrete sample prepared with 15% partial replacement achieved the specified minimum compressive strength after 56 days. From 15% replacement, there is then a gradual drop in its compressive strength, and the specified minimum strength was not achieved even after a curing time of 56 days it was found that the maximum strain of the concrete was replaced with a powder pumice stone is lower than conventional concrete. Based on the above property, it indicates the suitable pumice powder as a cementitious supplementary material in various concrete construction.